Adoptive transfer of ex vivo expanded SARS‐CoV‐2‐specific cytotoxic lymphocytes: A viable strategy for COVID‐19 immunosuppressed patients?. Issue 4 (31st March 2021) - Guerreiro, Manuel; Aguilar‐Gallardo, Cristóbal; Montoro, Juan; Francés‐Gómez, Clara; Latorre, Víctor; Luna, Irene; Planelles, Dolores; Carrasco, María Paz; Gómez, María Dolores; González‐Barberá, Eva María; Aguado, Cristina; Sempere, Amparo; et al.
Abstract: Cellular and humoral response to acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infections is on focus of research. We evaluate herein the feasibility of expanding virus‐specific T cells (VST) against SARS‐CoV‐2 ex vivo through a standard protocol proven effective for other viruses. The experiment was performed in three different donors' scenarios: (a) SARS‐CoV‐2 asymptomatic infection/negative serology, (b) SARS‐CoV‐2 symptomatic infection/positive serology, and (c) no history of SARS‐CoV‐2 infection/negative serology. We were able to obtain an expanded VST product from donors 1 and 2 (1.6x and 1.8x increase of baseline VST count, respectively) consisting in CD3 + cells (80.3% and 62.7%, respectively) with CD4 + dominance (60% in both donors). Higher numbers of VST were obtained from the donor 2 as compared to donor 1. T‐cell clonality test showed oligoclonal reproducible peaks on a polyclonal background for both donors. In contrast, VST could be neither expanded nor primed in a donor without evidence of prior infection. This proof‐of‐concept study supports the feasibility of expanding ex vivo SARS‐CoV‐2‐specific VST from blood of convalescent donors. The results raise the question of whether the selection of seropositive donors may be a strategy to obtain cell lines enriched in their SARS‐CoV‐2‐specificity for future adoptive transfer to immunosuppressed patients.